Perancangan Sistem Safety Shut Off Valve pada Tabung LPG untuk Mencegah Bahaya Kebocoran Gas - Fitri Rahmah; Adi Wiyono (Fakultas Teknik - Universitas Bung Karno, 2023)
The program to convert kerosene to LPG (Liquefied Petroleum Gas) launched by the government since 2007 has had a positive impact, among other things because energy consumption has become more economical and use is relatively cleaner and easier. However, this program has negative impacts, including the potential for explosion and fire hazards due to gas leaks in the cylinders. Factors that can cause leaks in LPG cylinders are improper installation of the regulator, poor quality cylinder sealing rings, and even regulators that do not have the Indonesian National Standard (SNI). Seeing the potential for great danger due to gas leaks in LPG cylinders, the solution that can be implemented is to build a safety shut off valve system on LPG cylinders. In this paper, a safety shut off valve system is described which is designed and placed in the tube regulator section. System test results with an LPG gas concentration of 5000 ppm (parts per million) show that the average response time of the system in automatically activating the safety shut off valve is 0.55 seconds. The accuracy value of the designed system is shown through comparison with the results of mathematical calculations, namely having an error in the range of 1.76 percent - 3.43 percent at a sensor reading distance of 0 - 100 cm.